Kelembagaan Politik Islam: Konsep Konstitusi, Legislasi, Demokrasi, Ummah Dan Syura’ - Kun Budianto (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2017)
Islam is a religion perfect and comprehensive, it should have a major role in the political life of a country. To go toward the integration of society, the state and the Islamic ijtihad is needed that will provide guidance for parliamentarians or politicians in explaining hujahnya in politics. And the interaction of Muslims living in the modern world with the political will give new experiences and challenges towards a just and prosperous society. A clean and healthy politics will increase public confidence, especially in Indonesia that Islam is indeed manage all aspects from the economic, social, military, cultural to political. Political institutions in Islam, among others, consists of the concepts of the constitution, legislation, shura and democracy and also the ummah. Islam made ​​in the constitution is in order as the guidelines and rules of the game in the relationship between government and the people. Legislation created to deal with affairs of state and government set a law that will be enforced and implemented by people. While the shura and democracy are two interrelated things, shura is in deliberation and democracy also emphasizes the element of deliberation. And the ummah or community can be defined nation, people, people, communities and so on. It could be said that the people of an organization are bound by the rules of Islam.